Factors contributing to motorcycle accidents in Malaysia. (November 2019) - Idris, Anas; Hamid, Hussain; Teik Hua, Law
Abstract: Road accident in Malaysia is a major issue and the rate of accident is increasing yearly as per demonstrate by the indicator published by the relevant authority. A prompt action on this issue is vital because road accident and fatalities contribute to the loss in term of economic to the country. Statistic by Road Transport Department, Malaysia show the ratio of each Malaysian own a vehicle is mostly equal to one. Fatalities due to road accident has become a worldwide issue and more than 1.25 million people died due to road accident every years. Motorcycle is a popular mode of transport in Malaysia compare to other mode of transportation and the numbers of fatalities & road accident involve motorcyclist & pillion is an alarming and need to be address effectively by the relevant authority. This paper aim is to review the scenario of road accident happen in Malaysia especially event involving motorcyclist and pillion. It's will discuss on the factor that cause the road accident happen based on the statistic produce by the relevant authority and research done on the matter. Road safety research is important to enable a reliable strategies can be develop to mitigate the cause of road accident and reduce the number of fatalities. Providing safer and forgiving road is required to reduce risk of fatalities / injuries to motorcyclist and pillion if involve in road accident.